EPİLEPSİ HASTALARINDA UBİKUİTİN C-TERMİNAL HİDROLAZ-L1 GEN POLİMORFİZMİ VE EPİLEPTİK ATAK SIRASINDA VE REMİSYON DÖNEMİNDEKİ UBİKUİTİN C-TERMİNAL HİDROLAZ-L1 ENZİMİNİN DÜZEYİNİN ARAŞTIRILMASI - YASAK, İBRAHİM HALİL (Fırat Üniveristesi, 2016)
Ubikuitin C-Terminal hidrolaz – L1 (UCH-L1) enziminin epilepsi hastalarında düzeyinin tespiti, epileptik atak (konvulziyon), remisyon dönemi ve sağlıklı bireylere göre değişiminin tespit edilmesi ve epilepsi hastalarında UCH-L1 genin S18Y polimorfizmin araştırılması amaçlandı. Çalışmamızda 80 (E/K= 55/25) epileptik atak, 80 (E/K=39/41) remisyon döneminde epilepsi hastası olan toplam 160 (E/K= 94/66) epilepsi hastası ile 100 (E/K=59/41) sağlıklı gönüllünün UCH-L1 enzim düzeyleri karşılaştırıldı. Ayrıca epilepsi hastaları epilepsi sebebine göre 110 esansiyel (E/K=64/46) ve 50 kazanılmış (E/K=30/20) epilepsi olanların verileri de analiz edildi. UCH-L1 enzim düzeyleri; epilepsi hastalarında 8,30 (IQR=6,57-11.40) ng/mL ile sağlıklı gönüllülerde ise 3,90 (IQR=3,31-7,22) ng/mL olduğu ve epilepside anlamlı oranda arttığı tespit edildi (p<0,001). UCH-L1 düzeylerinin epileptik atak 8,50 (IQR=6,93-11,16) ng/mL ile remisyon döneminde 8,10 (IQR=6,22-11,93) ng/mL anlamlı bir fark oluşturmadığı tespit edildi (p= 0,6123). Ayrıca kazanılmış epilepside 9,71 (IQR=7,77-13,04) ng/mL, esansiyel epilepsi de ise 7,90 (IQR=6,26-11,03) ng/mL olduğu ve kazanılmış epilepside anlamlı oranda arttığı edildi (p=0,0067). Receiver Operating Characteristic (ROC) Curve analizinde UCH-L1 cut-off değerini 4.34 ng/mL olarak aldığımızda epilepsi hastaları için sensitivite %93.75, spesifite %66.00 (AUG=0.801, p<0.0001, %95 CI: 0.747 to 0.848) olduğu tespit edildi. Epilepsi nedeni esansiyel olan 97 (E/K=57/40) hasta ile 94 (E/K=55/39) sağlıklı gönüllü arasındaki UCH-L1 genin S18Y polimerimi açısından anlamlı bir fark olmadığı tespit edildi (X2= 5,692, p=0,058). Ayrıca epilepsi hastaları arasında UCH-L1 genin S18Y polimorfizmin cinsiyete göre de değişmediği saptandı (X2= 3,633, p=0,163). Sonuç olarak UCH-L1 düzeyi epilepsi hastalarında sağlıklı bireylere göre anlamlı oranda artmakta iken epileptik atak ve remisyon dönemlerinde fark oluşturmamaktadır. Ayrıca UCH-L1 genin S18Y polimorfizmin epilepsi ile sağlıklılar arasında anlamlı bir fark oluşturmamaktadır.

It found in almost all the neurons in the central nervous system ubiquitin C-terminal hydrolase - L1 (UCH-L1) and to determine the level of this enzyme levels in epileptic patients, epileptic seizure (convulsions) and remission detection of changes compared to healthy group. Often used in studies aimed to investigate UCHL1 the gene S18Y polymorphism in patients with epilepsy. At this stage 80 (M/F= 55/25) epileptic attacks, 80 (M/F=39/41) patients in remission a total of 160 (M/F= 94/66) epilepsy patients and 100 (M/F=59/41) healthy volunteers UCH-L1 levels were compared. In addition, patients with epilepsy was created as a separate group according to the cause of epilepsy as 110 essential and 50 acquired epilepsy and analyzed the data. Ubiquitin C-terminal hydrolase - L1 enzyme levels of epilepsy patients and healthy group were compared to the results of the analysis 3.8990 (IQR=3.3080-7.2195) ng/mL and were found to have a significantly increased of epilepsy (p=<0,001). However, the levels of UCH-L1 in patients with epilepsy were found not a significant difference between epileptic attack 8.500 (IQR=6.926-11.160) ng/mL and remission patients 8.105 (IQR=6.223-11.931) ng/mL (p= 0,6123). In the comparisons of we made separate group according to the cause of epilepsy were found significantly increased in essential 9.7125 (IQR=7.7700-13.0440) ng/mL according to an acquired epilepsy 7.9040 (IQR=6.2640-11.0270) ng/mL (p=0,0067). We have received the value of ubiquitin cut-off as a 4.336 ng/mL for the ROC Curve analysis and were found sensitivity of epilepsy %93.75, specificity %66.00 (AUG=0.801, p<0.0001, %95 CI: 0.747 to 0.848). In the second stage of our work we compared UCH-L1 gene S18Y polymorphism between epilepsy attacks of epilepsy patients, remission patients a total of 97 (M/F=57/40) epilepsy patients and 94(M/F=55/39) healthy volunteers (X2= 5,692, p=0,058). According to the result of the analysis were found there is not a significant difference in UCH-L1 gene S18Y polymorphisms between epilepsy patients and healthy group. In addition, UCHL1 gene S18Y polymorphisms have been found not to change with the gender (X2= 3,633, p=0,163). As a result, UCH-L1 level was significantly increased in epileptic patients compared to healthy group, but there is no difference between epileptic seizures in epileptic patients and patients in remission.
Epilepsy patients in the ubiquitin c-terminal hydrolase-L1 gene polymorphism and during epileptic attack and remission of ubiquitin C-terminal hydrolase-L1 analysis of the level of enzyme
Keywords: İlk ve Acil Yardım